2020
DOI: 10.1101/2020.07.20.211441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Splicing Factor XAB2 interacts with ERCC1-XPF and XPG for RNA-loop processing during mammalian development

Abstract: RNA splicing, transcription and the DNA damage response are intriguingly linked in mammals but the underlying mechanisms remain poorly understood. Using an in vivo biotinylation tagging approach in mice, we show that the splicing factor XAB2 interacts with the core spliceosome and that it binds to spliceosomal U4 and U6 snRNAs and pre-mRNAs in developing livers. XAB2 depletion leads to aberrant intron retention, R-loop formation and DNA damage in cells. Studies in illudin S-treated cells and Csbm/m developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
1
0
0
Order By: Relevance
“…On the other hand, it was shown that splicing inhibitors cause exon-skipping changes which affect transcripts of DNA repair genes, such as CHEK2 16,19 . The latter mechanism is in good agreement with the fact that spliceosomal proteins play an important role in preventing DNA damage through their splicing-dependent or independent functions [20][21][22][23][24] . Additionally, the extensive study of splicing inhibitors on leukemia cell lines poses challenges in comprehensively understanding general molecular mechanisms partly due to the high frequency of splicing factor mutations in this malignancy.…”
Section: Introductionsupporting
confidence: 84%
“…On the other hand, it was shown that splicing inhibitors cause exon-skipping changes which affect transcripts of DNA repair genes, such as CHEK2 16,19 . The latter mechanism is in good agreement with the fact that spliceosomal proteins play an important role in preventing DNA damage through their splicing-dependent or independent functions [20][21][22][23][24] . Additionally, the extensive study of splicing inhibitors on leukemia cell lines poses challenges in comprehensively understanding general molecular mechanisms partly due to the high frequency of splicing factor mutations in this malignancy.…”
Section: Introductionsupporting
confidence: 84%